Perlindungan Hukum Bagi Korban Tindak Pidana Cyber Scam Serta Dampaknya Bagi Korban Sebagai Bentuk Viktimisasi Sekunder - An Nisya Nursabilah; Nazmi Viranha Khurulani; Anggia Prasanti; Dea Aulia Zuhra; Allyah Alicia Hg; Nabila Nabanurohmah (Hukum Inovatif : Jurnal Ilmu Hukum Sosial dan Humaniora, 2025)
The rapid development of digital technology has increased the potential for cybercrime, including cyber scams, which cause major losses to victims both materially and psychologically. In this context, the state is obliged to provide legal protection to victims, but in practice there are still many legal gaps and suboptimal implementation. This study aims to analyze the form of legal protection for victims of cyber scam crimes and the impact of these crimes in triggering secondary victimization. This study uses an empirical legal method with a descriptive-analytical approach that combines primary data from observations and interviews as well as secondary data from legal literature and laws and regulations. The results of the study show that although there is a legal umbrella such as the ITE Law and the Witness and Victim Protection Law, the victim protection mechanism has not been running effectively. The contribution of this study provides urgency for improving regulations and implementing victim-oriented legal protection, as well as the importance of digital literacy and empathy for law enforcement in handling cybercrime cases.